Coupled fluid-structure interactions using the fast multipole method - Wilkes, Daniel; Duncan, Alexander (The Australian Acoustical Society, 2011)
The interaction of sound with an arbitrarily shaped underwater object must in general be treated as a coupled interaction between the fluid and structure, due to the acoustic impedance properties of water. Typically, this type of problem is solved by building a numerical model of the exterior fluid and interior solid regions and then simultaneously solving the coupled system of equations, on the common fluid-structure interface. These models are restricted by their high cost in terms of computational time and memory. The fast multi pole method (FMM) significantly reduces these requirements and is applicable to many types of boundary integral equations. For simple structures, a coupled model using the FMM for both the fluid and structure will provide a substantial increase in the possible model size or frequency limit compared to traditional methods. This paper discusses stich a model and presents initial non-coupled results in the form of acoustic scattering and target strength results for the rigid BeTSSi submarine model.